2018
DOI: 10.1103/physrevb.97.064204
|View full text |Cite
|
Sign up to set email alerts
|

Counting local integrals of motion in disordered spinless-fermion and Hubbard chains

Abstract: We develop a procedure which systematically generates all conserved operators in the disordered models of interacting fermions. Among these operators, we identify and count the independent and local integrals of motion (LIOM) which represent the hallmark of the many-body localization (MBL). The method is tested first on the prototype disordered chain of interacting spinless fermions. As expected for full MBL, we find for large enough disorder NM = 2 M − 1 independent and quasi-local LIOM with support on M cons… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
46
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 64 publications
5
46
0
Order By: Relevance
“…This implies that only partial (charge) MBL may occur in the SU(2) symmetric Hubbard chains. This scenario is consistent with the number of local integrals of motion [57] which stays well below the value expected for systems with full MBL. Moreover, one cannot exclude that coupling of localized charges and delocalized spins will eventually delocalize also the charge degrees of freedom [58], even if the latter delocalization will happen at exceedingly long time-scales.…”
supporting
confidence: 82%
“…This implies that only partial (charge) MBL may occur in the SU(2) symmetric Hubbard chains. This scenario is consistent with the number of local integrals of motion [57] which stays well below the value expected for systems with full MBL. Moreover, one cannot exclude that coupling of localized charges and delocalized spins will eventually delocalize also the charge degrees of freedom [58], even if the latter delocalization will happen at exceedingly long time-scales.…”
supporting
confidence: 82%
“…It has also been found that MBL prevents a driven system from heating [9,[36][37][38][39][40][41]. These unusual properties can be explained via the existence of a macroscopic number of local integrals of motion [12,25,26,[42][43][44][45][46][47].While most of theoretical studies so far concentrated on the one-dimensional (1D) disordered model of interacting spinless fermions, the experiments on MBL are performed on cold-fermion lattices [14,[48][49][50] where the relevant model is the Hubbard model with spin-1/2 fermions, whereby the disorder enters only via a random (or quasi-periodic) charge potential. Recent numerical studies of such a model [47,[51][52][53] reveal that even at strong disorder, localization and nonergodicity occurs only in the charge subsystem, implying a partial MBL.…”
mentioning
confidence: 99%
“…Many-body localization (MBL) [1,2] is a robust phenomenon of ergodicity breaking in disordered interacting quantum many-body systems [3][4][5][6]. It has attracted considerable attention over the last decade, notable findings include an emergent integrability of MBL phase due to the existence of local integrals of motion (LIOMs) [3,[7][8][9][10] and an associated unbounded logarithmic growth of the bipartite entanglement entropy after a quench from a separable state [11,12]. A wide regime of subdiffusive transport on the ergodic side of the transition was found [13][14][15].…”
mentioning
confidence: 99%